NGAJI ONLINE: Transformasi Ngaji Kitab di Media Sosial - Evi Fitriana; Muhamad Khoiri Ridlwan (Institut Agama Islam Negeri Ponorogo, 2021)
Social change includes elements of both material and non-material culture. This emphasizes the great influence of material elements of culture on non-material elements. Technological developments cause cultural changes.The digital era has an impact on shifting interest in the search for Islamic knowledge from offline to online systems. Therefore, religious learning becomes easy and practical. The transfer of Islamic religious knowledge in “ngaji online